Visual Experiential and Art Practices in Cultural Context through Studies on the Megalithic Forms of Kelabit Highlands - Doris, Maying (Universiti Malaysia Sarawak (UNIMAS), 2019)
This research is purposely aimed to seek the relationship and the potential of visual experiential as well as art practices in cultural context through the case study onto the megalithic forms of Kelabit Highlands. Visual engagements in the cultural studies such as in anthropological study are often overlooked by the researcher and this particular domain is continuously misrepresented. Meanwhile, the artists are always being criticized for their inappropriate creative employment of culture into their personal artwork concerning the misleading concept and ideas for the audience to interpret. Thus, visual experiential and art practices were conducted by employing practice-based research onto the megalith structures of the Kelabit Highlands. Additionally, this research will apply new method for cultural appropriation known as ICE model consisting of internal, context and external factors as a mean of adaptating selected visuals to compliment the content by the art practitioner or researcher. Through the application of visual experiential and art practices with ICE in cultural context as the approaches in the adaptation of the cultural subject have aided towards enhancing the study and also cultural representation for the megaliths. The effectiveness of these methods has been tested by extending its application to exhibitions that is highlighting the Kelabit megaliths and potentially into the other field of visual research area. It is hoped that this research will contribute to the enhancement of cultural representation through the effectiveness methods in visual research. Nevertheless, it is also hoped that for future research recommendations visual arts should offer more beneficial roles particularly in documenting and disseminating cultural knowledge back to the community.